The Relationship Between Human Host and Environmental Factors on the Severity of Pneumonia Among Under-Five Children in West Java Province - Nadia Regita Ayu Cahyani; Hartati Eko Wardani; Lucky Radita Alma (Association of Public Health Scholars based in Faculty of Public Health, Sriwijaya University, 2023)
Pneumonia cases in West Java Province 2018 were ranked first as the province with the highest number of cases in Indonesia with a prevalence of 58.80%. About 7-13% of severe pneumonia patients with an increased risk of death in children require intensive care. This study aims to determine the relationship between host and environmental factors on the severity of pneumonia in children under five years. The research method used cross-sectional study design approach. Data analysis techniques used chi-square, fisher's exact, and multiple logistic regression tests. The population in this study was 2,338 children under five years aged 12-59 months in West Java Province for the 2018 period, while the sample consisted of 132 respondents who met the inclusion criteria and were recorded in RISKESDAS 2018. The results showed that there was a significant relationship between host factors and the severity of pneumonia, namely prematurity (aOR= 2.446; 95% CI=1.113-5.376), while environmental factors that have a significant relationship on the severity of pneumonia, namely the habit of opening windows (aOR= 2.963; 95% CI=1.342-6.544). There is no relationship between Low Birth Weight (LBW), home ventilation conditions and lighting intensity. The most dominant factor in the severity of pneumonia is that the habit of opening windows does not meet the risk of 2.9 times higher severity of pneumonia in children under five years. This study concludes a relationship between prematurity and the habit of opening windows on the severity of pneumonia.